Indonesian Maritime E-Leadership Training Towards a Digital-Based Marine Transportation System - Ningrum Astriawati; Prasetya Sigit Santosa; Waris Wibowo; Benny Hartanto; Yudhi Setiyantara (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
In the era of digitalizing, a leader is needed who can provide clear direction and goals and understand digital development technology. The development of digital-based information systems in the transportation sector will have an impact on reducing logistics costs. For this reason, digital-based leadership is needed in all sectors, including the maritime sector. The purpose of this community service is to conduct Indonesian maritime e-leadership training toward a digital-based marine transportation system. The purpose of this e-leadership training is to increase knowledge of leadership ethos, increase leadership talents and interests, increase leadership creativity and reasoning power, and cultivate the spirit of community insight. Community service model in the form of training and service to the community. The training was carried out online and was attended by 531 students divided into 4 sessions, session I as many as 178 students, session II as many as 122 cadets, session 3 as many as 102 and session 4 as many as 129 cadets. The results of the service obtained that the benefits of Indonesia's maritime e-leadership training towards a digital-based marine transportation system are an increase in knowledge of leadership ethos, an increase in leadership talents and interests, an increase in leadership creativity and reasoning power, and fostering a spirit of community insight with an average answer of 73.04%, agreeing by 22.79% and disagreeing by 4.17%.